Clinical Applicability of Various Treatment Approaches for Upper Gastrointestinal Submucosal Tumors. (11th January 2016) - Zhang, Jing; Huang, Kaili; Ding, Shigang; Wang, Ye; Nai, Te; Huang, Yonghui; Zhou, Liya
Abstract : Submucosal tumor (SMT) is a disease that is commonly discovered during endoscopic examination. With advances in endoscopic ultrasonography (EUS) technology, this technique has become the primary screening method for the diagnosis of upper gastrointestinal SMTs. The present study summarized the clinical data of patients who were examined and diagnosed with upper gastrointestinal SMTs by EUS, underwent endoscopic therapy or surgical treatment, and received final pathological results in our hospital between January 2011 and September 2014. Our results show that endoscopic therapy has become the main approach for the treatment of upper gastrointestinal SMTs with the development and maturation of endoscopic technology in recent years. Our conclusion suggests that the selection of endoscopic methods, such as endoscopic mucosal resection (EMR), endoscopic submucosal dissection (ESD), and peroral submucosal tunneling endoscopic resection (STER), under the guidance of EUS is safe and effective for the treatment of upper gastrointestinal SMTs.